"(Un)leashed" word: analysis of "en flecha", by Esther Ramón - Arroyo Martín, Juan (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This essays analyzes en flecha (2017) by the madrilenian poet Esther Ramón. The work draws from the notion of lenguaje as a creator of worlds. Esther Ramón’s poetry proposes a rupture from its root, that opposes the instrumental and representational lenguaje of logical reason. Thus, her poetic word is perceived as a flowing or becoming from an original bottom (where formes are born and break down simultaneously), which is inapprehensible by lenguaje and whose manifestation is seen like a common pain or void that breaks through corps, even though uniting them too.